A pilot study using financial transactions' spatial information to define high-risk neighborhoods and distribution pattern of COVID-19. (February 2022) - Mohammadi, Esmaeil; Azmin, Mehrdad; Fattahi, Nima; Ghasemi, Erfan; Azadnajafabad, Sina; Rezaei, Negar; Rashidi, Mohammad-Mahdi; Keykhaei, Mohammad; Zokaei, Hossein; Rezaei, Nazila; Haghshenas, Rosa; Kaveh, Farzad; et al.
Background: Development of surveillance systems based on big data sources with spatial information is necessitated more than ever during this pandemic. Here, we present our pilot results of a new technique for the incorporation of spatial information of transactions and a vital registry of COVID-19 to evaluate the disease spread. Methods: We merged two databases of laboratory-confirmed national COVID-19 registry of Iran and financial transactions of point-of-sale devices from February to March 2020 as our training data sources. Spatial information was used for the visualization of maps and movements of sick individuals. We used the point-of-sale devices-related guild to check for the dynamics of financial transactions and effectiveness of quarantines. Findings: In the study period, 174, 428 confirmed cases were in the COVID-19 registry with accompanying transactions information. In total, 13, 924, 982 financial transactions were performed by them, with a mean of 1.2 per day for each person. All guilds had a decreasing pattern of "risky" transactions except for grocery stores and pharmacies. The latter showed a decreasing pattern by impose of lockdowns. Different cities were the hotspot of disease transmission as many "high-risk" transactions were performed in them, among which Tehran (mainly its central neighborhoods) and southern cities of Lake Urmia predominated. Lockdowns indicated that the disease gradually became less transmissible. Interpretation: Financial transactions can be readily used for epidemics surveillance. Semi real-time results of such iterations can be informative for policy makers, guild owners, and general population to prepare safer commuting and merchandise spaces.